ANALISIS TOKOH DALAM CERPEN MALING 2 KARYA KOMALA SUTHA - Nessy; Wahyu Lestari, Mega; Suciati, Leni (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2025)
Short stories are a form of art that functions as a reflection of life. Through his imagination, a writer feels compelled to document various life events, so that his work can be enjoyed, understood, and appreciated by various groups. This study aims to analyze the character aspects in the short story Maling 2 by Komala Sutha. The story tells of a girl who lives in a village and has a lover. In the village where she lives, there are a series of theft cases that befall residents, even the main character's uncle is also a victim of theft. A scientific approach is used as a research method to collect data with the aim of obtaining useful results. Based on the analysis conducted, it was found that the main character has a significant influence on the perpetrator of the theft, encouraging him to carry out the action in order to fulfill the needs or desires of the main character.